2014
DOI: 10.3389/fneur.2014.00169
|View full text |Cite
|
Sign up to set email alerts
|

A Hypothesis Regarding the Molecular Mechanism Underlying Dietary Soy-Induced Effects on Seizure Propensity

Abstract: Numerous neurological disorders including fragile X syndrome, Down syndrome, autism, and Alzheimer’s disease are co-morbid with epilepsy. We have observed elevated seizure propensity in mouse models of these disorders dependent on diet. Specifically, soy-based diets exacerbate audiogenic-induced seizures in juvenile mice. We have also found potential associations between the consumption of soy-based infant formula and seizure incidence, epilepsy comorbidity, and autism diagnostic scores in autistic children by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 110 publications
1
15
0
Order By: Relevance
“…In the present study, it seems that the soy extract compensated the effects of deletion of ovarian hormones to increase the seizure score which was similar to the effects which was seen in our previous study that the soy extract fastened the seizure onsets [35]. Westmark also suggested that soy has a pro-convulsant effect which is mediated through glutamate and estrogen receptors [67,68].…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, it seems that the soy extract compensated the effects of deletion of ovarian hormones to increase the seizure score which was similar to the effects which was seen in our previous study that the soy extract fastened the seizure onsets [35]. Westmark also suggested that soy has a pro-convulsant effect which is mediated through glutamate and estrogen receptors [67,68].…”
Section: Discussionsupporting
confidence: 89%
“…While 21 serum metabolites were differentially abundant (eight identified) in oASD mice versus oTD mice, only genistein is significantly different in both colon contents and serum (Figures 4C,4F,and 4J). Various sexually dimorphic effects on neurodevelopment and behavior are linked to genistein, daidzein, and their degradation products (Ponti et al, 2017;Rodriguez-Gomez et al, 2014;Westmark, 2014). Elevated levels of these metabolites suggest reduced dietary nutrient metabolizing bacteria in the oASD microbiota (Matthies et al, 2008(Matthies et al, , 2009.…”
Section: Microbiota From Td-and Asd-colonized Mice Produce Discrete Mmentioning
confidence: 99%
“…Westmark et al showed that the isoflavones in soybeans are effective in decreasing the threshold of seizure in mouse models and, therefore, they may increase the risk of epilepsy (32). Westmark's hypothesis declares that the soy phytoestrogens interact with the metabotropic glutamate receptor and stimulate the production of the synaptic proteins that play a key role in reducing the seizure threshold (33).…”
Section: Discussionmentioning
confidence: 99%